(3cJGH GdSHYjfs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3eMeO Hf CMeO s)
(3ChdgG (B:s
(3GdMeO ddg TcQkG Ydi eG hgH dfG hHYO Cf Gddg GNJVG ef aVdg eG efYg ZjQfG cJGH GddGghJ s
(3BNQgG (B:s
(3hgPg GdcJH GdSHYjf jfHZi Cf JbQC ef ChdgG Edi BNQgG hCf jchf bGQFgG aeGgekG HgG dLejY eYGfjgG GdeHJOOI JeJ GdebGdI GdSHYhf hjJe HJeGegG GdcJGH s
(3hgh YHGQI Yf SHYhf ebGdI ai UfYI GdMjhGf hGdCTLGQ hGdCMLGQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1424s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs